The therapeutic role of γδT cells in TNBC - Li, Wenjing; Zhao, Xian; Ren, Chuanxin; Gao, Shang; Han, Qinyu; Lu, Min; Li, Xiangqi (Frontiers in Immunology, 2024)
Triple-negative breast cancer (TNBC) is a subtype of breast cancer that presents significant therapeutic challenges due to the absence of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2) expression. As a result, conventional hormonal and targeted therapies are largely ineffective, underscoring the urgent need for novel treatment strategies. γδT cells, known for their robust anti-tumor properties, show considerable potential in TNBC treatment as they can identify and eliminate tumor cells without reliance on MHC restrictions. These cells demonstrate extensive proliferation both in vitro and in vivo, and can directly target tumors through cytotoxic effects or indirectly by promoting other immune responses.Studies suggest that expansion and adoptive transfer strategies targeting Vδ2 and Vδ1 γδT cell subtypes have shown promise in preclinical TNBC models. This review compiles and discusses the existing literature on the primary subgroups of γδT cells, their roles in cancer therapy, their contributions to tumor cell cytotoxicity and immune modulation, and proposes potential strategies for future γδT cell-based immunotherapies in TNBC.